2004
DOI: 10.1002/ange.200453916
|View full text |Cite
|
Sign up to set email alerts
|

The Pristine Oil/Water Interface: Surfactant‐Free Hydroxide‐Charged Emulsions

Abstract: Emulsionen von Öl in Wasser sind in alkalischer Lösung auch ohne Tenside stabil. Die durch Anlagerung von Hydroxidionen erzeugte Oberflächenladungsdichte (siehe Bild) bestimmt man aus der elektroakustisch ermittelten Tröpfchengröße und der Menge an NaOH, die benötigt wird, um den pH‐Wert während der Homogenisierung konstant zu halten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
43
4
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 16 publications
11
43
4
1
Order By: Relevance
“…Numerous experimental studies have revealed that inert surfaces show a negative surface charge in neutral solutions and isoelectric points (IEP) close to pH 4. Similar characteristics were observed in experiments with oil/water [10][11][12][13][14] and gas/water [15][16][17][18][19][20] interfaces.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Numerous experimental studies have revealed that inert surfaces show a negative surface charge in neutral solutions and isoelectric points (IEP) close to pH 4. Similar characteristics were observed in experiments with oil/water [10][11][12][13][14] and gas/water [15][16][17][18][19][20] interfaces.…”
Section: Introductionsupporting
confidence: 82%
“…Although the majority of integral experiments suggest a preferential adsorption of hydroxide ions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], an opposite picture has emerged from experiments analyzing molecular structures and MD simulations [21•-26]. These studies concluded that the concentration of hydronium ions, but not hydroxide ions, is enhanced at the gas/water interface [21•-26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High or low pH could be expected to increase not only the deprotonation or protonation of acid and base groups, respectively, at the oil interface but also their site densities due to preferential migration from the oil bulk to the surface and reorientation there. Further, surprisingly large negative at high pH are observed for a wide range of nonpolar phases (air, oils and hydrophobic polymers) in 1:1 electrolytes [35,66,67]. Preferential adsorption of hydroxide ions is believed to be the cause, and may operate at crude oil interfaces, reinforced by hydroxide affinity for acidic groups on asphaltenes and resins.…”
Section: Further Considerationsmentioning
confidence: 99%
“…Although alcohol seems to have a dominant effect on the self-assembly, it is also known that oil in contact with water acquires a negative net charge due to accumulation of hydroxide anions. [10] So, the role of the attractive electrostatic forces between oppositely charged interface and the NPs in formation of well-ordered NP arrays should not be excluded.…”
mentioning
confidence: 99%